2022
DOI: 10.1021/acsomega.2c02663
|View full text |Cite
|
Sign up to set email alerts
|

Humic Acid Improves Greenhouse Tomato Quality and Bacterial Richness in Rhizosphere Soil

Abstract: Humic acid (HA) has attracted increasing attention as a new type of organic fertilizer in horticultural production, such as greenhouse-planted cherry tomato. However, we need more information to evaluate the effects of HA on soil rhizosphere bacteria and tomato performance under greenhouse conditions. In this study, greenhouse-planted cherry tomato was observed with HA added at dosages of 1500, 3000, 4500, and 6000 kg·ha –1 , respectively. The other two organic fertilizers [farmyard manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Organic fertilizers are rich in organic matter and various amino acids, which enhance soil fertility [13]. A meta-analysis indicated in that organic fertilizers could increase tomato yields by 42.18%, and soluble solids, soluble sugars, lycopene, and vitamin C were increased by 11.86%, 42.18%, 23.95%, and 18.97%, respectively, when compared to the control group [14], which is in agreement with the studies of Yang et al [15] and Sun et al [16]. The appropriate proportion of organic fertilizer substitution reduces rhizosphere soil nitrate nitrogen leaching [17].…”
Section: Introductionsupporting
confidence: 85%
“…Organic fertilizers are rich in organic matter and various amino acids, which enhance soil fertility [13]. A meta-analysis indicated in that organic fertilizers could increase tomato yields by 42.18%, and soluble solids, soluble sugars, lycopene, and vitamin C were increased by 11.86%, 42.18%, 23.95%, and 18.97%, respectively, when compared to the control group [14], which is in agreement with the studies of Yang et al [15] and Sun et al [16]. The appropriate proportion of organic fertilizer substitution reduces rhizosphere soil nitrate nitrogen leaching [17].…”
Section: Introductionsupporting
confidence: 85%
“…Few studies have evaluated the effect of humic acids on microbial diversity in plants. Sun et al (2022) verified that HA application in tomatoes resulted in the best flavor compared to the other two organic fertilizers. The Chaol estimator and Shannon index showed that fertilizer addition decreased microbial diversity but increased species richness.…”
Section: Resultsmentioning
confidence: 68%
“…There are many studies in the world on the development of vegetables by bacteria that promote plant growth that PGPB, i.e., potato, tomato, onion, pepper, beans, and lettuce (Zahran et al, 2020;Sun et al, 2022;de Andrade et al, 2023). Although previous researchers reported that plant growth-promoting bacteria vary in diverse agriculture crops and even in different varieties of the same crops (Ummara et al, 2022), only a few research papers have studied their effects on pea.…”
Section: Resultsmentioning
confidence: 99%